Unveiling Culinary Patterns: Implementation Of K-Means Clustering Algorithm on Food Products in Cafes - Gumelar, Lasmi Lasmini; Ruuhwan, Ruuhwan; Hikmatyar, Missi (Department of Informatics, Siliwangi University, Indonesia, 2023)
Barcode Se'i and Coffee is one of the cafes on JL. Major Utarya, No. 48, Empangsari, District. Tawang, Tasikmalaya. Barcode Se'i and Coffee is quite famous because the concept of the place is nice, comfortable, and instagrammable. Not only that, but the Barcode cafÃ© was also the first to create cow sei in Tasikmalaya. By analyzing the cafe menu groupings, information can be found regarding the level of menu sales. This type of analysis, capable of assessing sales levels, involves the use of data mining techniques such as clustering. Data mining is a data processing stage that aims to identify and extract patterns from a certain set of data. One of the methods included in data mining is the clustering technique. Reclassification techniques are used to group objects into several groups based on observed indicators, ensuring that all objects have a significant level of similarity compared to objects placed in different groups. With Rapidminer software and using the k-means algorithm with sales data for 11 months with the calculations carried out producing 5 clusters. Based on the comparison results of 3 K-Means algorithms with different K values, namely 3, 4, 5, the result from Davies Bouldin with a value close to 0 is a value with K 5, with the result from Davies Bouldin being - 0.912.